Analisis Implementasi Program Keterampilan dan Kegiatan Kerja Bagi Narapidana Studi Kasus Lapas Kelas I Tangerang - Manting, Lollong (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
The purpose of this research is first, to analyze the implementation of the program of activities and work skills for inmates at Tangerang Correction centre, second to analyze the effectiveness of the implementation of the program of activities and work skills, as well as the purpose of correctional services, namely to form the prisoners to become fully human beings, realize their mistakes, improve themselves, not repeat criminal acts, can play a role in development, can live normally as good and responsible citizens so that they can be accepted again by the community. The research method used in this research is qualitative research, arguing that the qualitative approach is related to the concepts and problems raised leading to the fact that the implementation of work activities programs in prisons. The conclusions from this research are first, the implementation/implementation of job training activities in the correction centre has been conducted well, secondly, the involvement or participation of convicts in work activities can be said to be quite optimal, while the obstacles found are the obstacles to implementing work skills activities are lack of ability to conduct market research, especially in determining the product to be developed, limited space to carry out work activities due to the impact of overcrowding, production activities in correctional institutions depend on the head of correctional Institutions and workshop staff so that skills and work experience are not standardized, production supervision tends to consider aspects of activities not a business aspect such as the need for product quality control, and existing marketing is still conventionally limited to the area around prisons.